Sparking deposited ZnO nanoparticles as double-layered photoelectrode in ZnO dye-sensitized solar cell - Kritsada Hongsith (2018)
The semiconducting layers of ZnO nanoparticles (ZN), ZnO powder (ZP) and ZnO nanopowder (ZNP) were designed and fabricated for double-layered semiconducting photoelectrode in dye-sensitized solar cells (DSSCs). The under-layer was ZN, which was prepared by simple and cost-effective sparking technique onto F-doped tin oxide (FTO) glass substrate and its thickness was controlled by number of sparking cycles for 0, 10, 25, 50 and 100 rounds under atmospheric pressure. Then, ZP or ZNP was screened on to ZN to form double-layered photoelectrode. Here, the DSSC structures were FTO/double-layered ZnO/Eosin Y/electrolyte/Pt counterelectrode. The best results of DSSCs were observed with Jscof 4.71 mA/cm2and 5.56 mA/cm2and photoconversion efficiency of 1.11% and 1.14% at 50 sparking cycles for ZP and ZNP over-layers, respectively. The efficiency enhancement can be explained by combination effects of electron and light scattering. Moreover, the modified equation of short circuit current density was developed and effectively used to explain the efficiency enhancement. © 2013 Elsevier B.V. All rights reserved.